Multi-axle actuator controller - Larsson, Simon (My University, 2012)
3D scanning is a useful technology, but it is very time consuming as the object needs to be scanned from every possible angle for the computer to be able to model the complete surface. One method to simplify this process is automated rotation and object scanning. This project shows reasearch and development of an actuator control system for controlling a platform for this purpose. Because we do not know what platform will be connected, the controller should be able to control a set of di erent actuators, and be con gurable for the kind of actuator currently connected. A protocol for communicating with the controller will be created, along with a graphical user interface. Integration with 3D scanning software is also examined.
Keywords: Data- och informationsvetenskap; Computer and Information Science